The Kanamari Body-Owner. Predation and Feeding in Western Amazonia - Luiz Costa (Journal de la Société des Américanistes)
The Kanamari Body-Owner. Predation and Feeding in Western Amazonia. This article is an ethnography of the Kanamari concept of -warah, a word that simultaneously means « living body », « owner » and « chief ». It aims to establish the relationship between these meanings through a focus on the replication of the -warah at different scales: from the body of individual persons, through the village chief, into the chief of a river basin. It is argued that each of these positions implies the capacity to familiarize its inverse through acts of feeding. In this way, and respectively, the soul, co-resident villagers and the people of a subgroup are made into component parts of their -warah in a process that is analogous to acts of familiarization that have been described for other parts of Amazonia.